World Athletics making contingency plans for heavy COVID-19 impact on 2021 competition schedule - Rowbottom, M. (inside the games, 2020)
World Athletics is working on contingency plans for a 2021 season where competition continues to be impacted by the COVID-19 pandemic in a similar way as 2020.